Skeletal deformities in Barbus xanthos (Teleostei: Cyprinidae) collected from the Dalaman River in southwestern Turkey - Jawad Laith; Güçlü Salim Serkan (Oceanological and Hydrobiological Studies)
In this study, skeletal anomalies such as vertebral centra deformation, lordosis (ventral curvature), and consecutive repetition of lordosis and kyphosis were examined in specimens of Barbus xanthos (Güçlü, Kalaycı, Küçük & Turan, 2020) collected from the Dalaman River, southwestern Turkey. Abnormalities of the vertebral column were observed in both thoracic and caudal vertebrae. Cases of lordosis and consecutive repetition of lordosis and kyphosis showed varying degrees of severity. Specimens with consecutive repetition of lordosis showed the most acute deformities among the cases studied, as they revealed complicated incidences of skeletal anomalies. None of the cases were fatal as they occurred in adult individuals. This study discusses the possible causes of such deformities and the usefulness of this type of study in environmental monitoring.